Analisis Deiksis Ruang Dalam Manga Doraemon Vol 1 (Chapter 1-3) Karya Fujiko F.Fujio - Habib Priatama; Damai Yani (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
The purpose of this is to describe spatial deixis in the manga Doraemon vol 1 (chapters 1-3) by Fujiko F. Fujio. The type of research used in this research is a qualitative approach. The results of this research show that there are 35 data containing types of spatial deixis and their uses, namely 26 pointing deixis, 3 situation deixis, 4 place deixis and 2 direction deixis. Meanwhile, for the type of spatial deixis, there are 18 data which are included in ninshou-gata and 17 data which contain enkin-gata.